2018
DOI: 10.3382/ps/pex319
|View full text |Cite
|
Sign up to set email alerts
|

Construction of multiple linear regression models using blood biomarkers for selecting against abdominal fat traits in broilers

Abstract: Plasma very low-density lipoprotein (VLDL) can be used to select for low body fat or abdominal fat (AF) in broilers, but its correlation with AF is limited. We investigated whether any other biochemical indicator can be used in combination with VLDL for a better selective effect. Nineteen plasma biochemical indicators were measured in male chickens from the Northeast Agricultural University broiler lines divergently selected for AF content (NEAUHLF) in the fed state at 46 and 48 d of age. The average concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Despite substantial heritability (h 2 , 0.40~0.53) [6,7], genetic progress in abdominal fat deposition has been slow due to the difficulty and cost of measuring this phenotype in a non-invasive manner [8]. In addition, the genetic selection against fatness is hindered by the high positive correlation between BW and abdominal fat content [9].…”
Section: Introductionmentioning
confidence: 99%
“…Despite substantial heritability (h 2 , 0.40~0.53) [6,7], genetic progress in abdominal fat deposition has been slow due to the difficulty and cost of measuring this phenotype in a non-invasive manner [8]. In addition, the genetic selection against fatness is hindered by the high positive correlation between BW and abdominal fat content [9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in broiler chicken farms a rapid increase in the growth rate of broiler chickens has been accompanied by an increase in the deposition of body fat [7]. Fat has been considered as a by-product of very little commercial value [8]. Moreover, excessive fat deposition can increase feed cost and reduce feed conversion efficiency [9].…”
Section: Introductionmentioning
confidence: 99%
“…We also estimated the correlation between plasma VLDL concentration and AF content (AFW and AFP), and the results indicated that plasma VLDL concentration was significantly correlated with AF content. This result was consistent with the previous report which also detected significant correlation between plasma VLDL concentration and AF content ( r = 0.46) in broilers (Dong et al, ). All these results indicated that the plasma VLDL concentration could reflect the AF content in chicken.…”
Section: Discussionmentioning
confidence: 99%
“…Selecting traits that are highly associated with AF might be one of the best methods. Plasma very low‐density lipoprotein (VLDL) concentration was detected to be significantly associated with AF and could be applied for commercial broiler breeding programmes (Crespo & Esteve‐Garcia, ; Dong et al, ; Griffin & Whitehead, ; Legrand & Hermier, ). Whitehead and Griffin () established two chicken lines divergently selected for AF by using plasma VLDL concentration as the selection criterion.…”
Section: Introductionmentioning
confidence: 99%